Perspective Intercultural Bioethics and Human Rights: the search for instruments for resolving ethical conflicts culturally based. - Aline ALBUQUERQUE (Universidade de Brasília, 2015)
This article aims to contribute to a deeper reflection on intercultural conflicts within the bioethics scope, and to point out the problem of using human rights as a theoretical normative mediator of the conflicts in bioethics that bear elements of interculturalism. The methodological steps adopted in this inquiry were: analysis of the concept of intercultural conflict in bioethics, from the perception developed by Colectivo Amani; study of human rights as tools of the culture of human beings, based on Bauman's and Beauchamp's theories; investigation of the toolsthat human rights offer so as to solve intercultural conflicts in bioethics. It was concluded that intercultural bioethics must incorporate to its prescriptive and descriptive tasks norms and institutions of human rights that ensure the participation and social integration of the individuals from communities that are in cultural conflict. Such measure will act as instrumentsfor the solution of intercultural conflicts.